SAT0320 Reliability analysis of the madrid sonographic enthesis index (MASEI) and different doppler subgroups in psoriatic arthritis. (12th June 2018) - Macía Villa, C.; Falcao, S.; De Miguel, E.
Abstract : Background: Enthesitis is the cornerstone of spondyloarthritis, and ultrasound (US) indexes have emerged in the last years being the Madrid Sonographic Enthesis Index (MASEI) one of the more widely used. Objectives: To evaluate the reliability of MASEI and different enthesis power doppler (PD) definitions in Psoriastic Arthritis (PsA). Methods: 27 consecutive non selected PsA patients were included. An US expert rheumatologist performed the MASEI examination using a MyLab 70 XVG machine, Esaote, Genova, Italy, with a greyscale (GS) 13 MHz probe and 7.1 MHz power Doppler (PD) frequency, PRF 750 Hz and 60 Gain. US images and 3–5 s videos were obtained in transversal and longitudinal views for further reliability analysis. The inter-reader reliability analysis was performed by three readers and true US result was the consensus of at least two of them. In addition to the PD item of MASEI (defined as signal in bone profile or intratendon or bursa on the enthesis area), three other PD definitions were evaluated as present or absent: PD OMERACT (PD signal at enthesis ≤2 mm to the bone profile), PD bursa (PD signal inside bursa) and PD tendon (PD signal in the enthesis tendon >2 mm from the bone profile). Intraclass correlation coefficient (ICC) estimations and 95% confident intervals were calculated for the reliability analysis of MASEI and PD subgroups based on a mean-rating ( k =3), absolute-agreement, two-way mixed effect model. Cohen`s Kappa test was used for analysis of MASEI's items reliability. SPSS statistical package version 20 (SPSS Inc, Chicago, IL) was used. Results: Inter-reader reliability of MASEI and PD subgroups is shown in table 1. PD bursa showed the lowest reliability. MASEI, PD MASEI, PD OMERACT and PD tendon showed good to excellent reliability, being PD tendon the best one. table 2 shows reliability data of each MASEI lesion in each enthesis included in the index. Best agreement percentages and kappa values were found in erosions and PD with mainly good to excellent data, while the worst ones were found in calcifications with poor to moderate values. Conclusions: MASEI has demonstrated to be a reliable tool in PsA. Erosions and PD showed the best reliability values. Evaluating different definitions of enthesis PD, signal in the tendon was the most reliable one, followed with minimal differences by PD MASEI and PD OMERACT, and in last place PD bursa. Disclosure of Interest: None declared